Antibody response following the third and fourth SARS-CoV-2 vaccine dose in individuals with common variable immunodeficiency - Nielsen, Bibi Uhre; Drabe, Camilla Heldbjerg; Barnkob, Mike Bogetofte; Johansen, Isik Somuncu; Hansen, Anne Kirstine Kronborg; Nilsson, Anna Christine; Rasmussen, Line Dahlerup (Frontiers in Immunology, 2022)
ABSTRACT: Background: The antibody response after vaccination is impaired in Common Variable Immunodeficiency (CVID). Objective: We aimed to study the spike receptor-binding domain IgG antibody (anti-S-RBD) levels during a four-dose SARS-CoV-2 vaccination strategy and after monoclonal antibody (mAB) treatment in CVID. Moreover, we assessed the anti-S-RBD levels in immunoglobulin replacement therapy (IgRT) products. Methods: In an observational study, we examined anti-S-RBD levels after the second, third and fourth dose of mRNA SARS-CoV-2 vaccines. Moreover, we measured anti-S-RBD after treatment with mAB. Finally, anti-S-RBD were assessed in common IgRT products. Antibody non-responders (anti-S-RBD <7.1) were compared by McNemar’s test and anti-S-RBD levels were compared with paired and non-paired Wilcoxon signed rank tests as well as Kruskal-Wallis tests. Results: Among 33 individuals with CVID, anti-S-RBD levels increased after the third vaccine dose (165 BAU/mL [95% confidence interval: 85; 2280 BAU/mL], p=0.006) and tended to increase after the fourth dose (193 BAU/mL, [-22; 569 BAU/mL], p=0.080) compared to the previous dose. With increasing number of vaccinations, the proportion of patients who seroconverted (anti-S-RBD ≥7.1) increased non-significantly. mAB treatment resulted in a large increase in anti-S-RBD and a higher median level than gained after the fourth dose of vaccine (p=0.009). IgRT products had varying concentrations of anti-S-RBD (p<0.001), but none of the products seemed to affect the overall antibody levels (p=0.460). Conclusion: Multiple SARS-CoV-2 vaccine doses in CVID, seem to provide additional protection, as antibody levels increased after the third and fourth vaccine dose. However, anti-S-RBD levels from mAB outperform the levels mounted after vaccination.